2001
DOI: 10.1021/ie0104565
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Desulfurization Process for Fuel Oils Based on the Formation and Subsequent Precipitation of S-Alkylsulfonium Salts. 5. Denitrogenation Reactivity of Basic and Neutral Nitrogen Compounds

Abstract: The denitrogenation behavior of several model nitrogen compounds has been investigated during a novel desulfurization and simultaneous denitrogenation process based on alkylation using CH3I and AgBF4 (alkylating agents) and subsequent precipitation of the resulting materials. The denitrogenation reactivities obtained for basic nitrogen compounds (aniline, pyridine, quinoline, and acridine) dissolved in xylene solution were compared to those for neutral compounds (pyrrole, indole, and carbazole). The basic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Their possible core structures are indole, carbazole, acridine, and their derivatives (see Figure e). Literature studies show that indole, carbazole, and their derivatives are difficult to be removed by HDN for their basicity lower than basic nitrogen species, such as quinoline. Although acridine belongs to basic nitrogen species, hydrodeoxygenation (HDO) of N 1 O 1 (DBE of 12) may contribute to its high content in hydrotreated shale oil.…”
Section: Resultsmentioning
confidence: 99%
“…Their possible core structures are indole, carbazole, acridine, and their derivatives (see Figure e). Literature studies show that indole, carbazole, and their derivatives are difficult to be removed by HDN for their basicity lower than basic nitrogen species, such as quinoline. Although acridine belongs to basic nitrogen species, hydrodeoxygenation (HDO) of N 1 O 1 (DBE of 12) may contribute to its high content in hydrotreated shale oil.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen compounds are then precipitated as N-methylated tetrafluoroborates. Denitrogenation of light oils and vacuum gas oil was successfully achieved by this method (Table ), and it was accompanied by alkylation of sulfur and aromatics. , Studies with model compounds revealed that aniline, pyridine, quinoline, and carbazole were removed as precipitates of their corresponding methylated products, while indole and pyrrole were removed as insoluble polymerized materials. In addition, denitrogenation of basic nitrogen compounds and compounds containing alkyl substituents was more effective than that of nonbasic nitrogen compounds.…”
Section: Chemical Conversion Followed By Separationmentioning
confidence: 99%
“…Alkylation as a reaction has been investigated for denitrogenation of light oils 131 and vacuum gas oil. 132 The nitrogen compounds are methylated and then removed by precipitation. The alkylating agents used were CH 3 I and AgBF 4 .…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…Basic nitrogen compounds can be removed using an ion-exchange resin, , by liquid/liquid extraction using volatile carboxylic acid, and by metal complexation . The simultaneous removal of sulfur- and nitrogen-containing compounds has been studied by alkylation and subsequent precipitation method using excess alkylating agents (CH 3 I and AgBF 4 ), and by combination of UV irradiation , or chemical oxidation with subsequent liquid−liquid extraction using an oil/acetonitrile two-phase system liquid/liquid extraction. One alternate approach to remove unwanted heterocyclic compounds is to use bacterial cells or enzymes as biocatalysts .…”
Section: Introductionmentioning
confidence: 99%